2011
DOI: 10.1177/0333102411399349
|View full text |Cite
|
Sign up to set email alerts
|

Cathodal transcranial direct current stimulation of the visual cortex in the prophylactic treatment of migraine

Abstract: Our results suggest that the application of cathodal stimulation over the V1 might be an effective prophylactic therapy in migraine, at least with regard to pain control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
159
1
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(168 citation statements)
references
References 29 publications
4
159
1
4
Order By: Relevance
“…tDCS is currently being investigated as a therapeutic instrument for varied neurological conditions, which includes major depression 14,15 , posttraumatic stress disorder 16 , craving for food 17 , marijuana 18 , alcohol 19 and smoking 20 , as well as pain 21 , tinnitus 22 , migraine 23 , epilepsy 24 , Parkinson's disease 25,26 , stroke rehabilitation 27,28 and cognitive dysfunction 6,29 . Table 1 shows the evidence-based tDCS electrode montages to be used as treatment for different clinical conditions.…”
Section: Representative Resultsmentioning
confidence: 99%
“…tDCS is currently being investigated as a therapeutic instrument for varied neurological conditions, which includes major depression 14,15 , posttraumatic stress disorder 16 , craving for food 17 , marijuana 18 , alcohol 19 and smoking 20 , as well as pain 21 , tinnitus 22 , migraine 23 , epilepsy 24 , Parkinson's disease 25,26 , stroke rehabilitation 27,28 and cognitive dysfunction 6,29 . Table 1 shows the evidence-based tDCS electrode montages to be used as treatment for different clinical conditions.…”
Section: Representative Resultsmentioning
confidence: 99%
“…However, inhibitory low frequency rTMS over the vertex had no superior therapeutic effect to sham stimulation, 151 and cathodal (inhibitory) tDCS over the occipital cortex had no signifi cant preventive effect on migraine attacks , although the latter intervention did reduce attack intensity compared with placebo. 152 By contrast, in a pilot trial designed to assess an alternative hypothesis-that the visual cortex is not hyperexcitable per se, but, rather, insufficiently activated at baseline (as described above 87 )-anodal (facilitatory) tDCS over the occipital cortex significantly decreased attack frequency and intensity when used as preventive therapy in patients with migraine. 150 The challenge for future research, therefore, lies in identification of the precise anatomical structures and functional networks involved in migraine, and determi nation of which pharmacological and nonpharmacologi cal interventions can optimally modulate the function of these areas and thereby improve temporal information processing.…”
Section: Prospects For Clinical Researchmentioning
confidence: 99%
“…Indeed, most of the public, are aware of electroconvulsive therapy (ECT), often referred to as "electroshock", and its deleterious effects on cognition (e.g., amnesia) [1]. However, in the new millennium a burst of studies using transcranial electric stimulation (TES) have demonstrated that the delivery of a low current of electricity to well-defined brain regions can positively a ect human mental health and well-being in areas such as pain [2], migraines [3] and psychiatric illnesses [4]. The aim of the current paper is to introduce TES methods within the framework of cognitive enhancement, a topic with important implications for translational neuroscience.…”
mentioning
confidence: 99%